Normal cardiovascular development in mice deficient for 16 genes in 550 kb of the velocardiofacial/ DiGeorge syndrome region - Puech, Anne (The National Academy of Sciences, 2000)
Hemizygous interstitial deletions in human chromosome 22q11 are associated with velocardiofacial syndrome and DiGeorge syndrome and lead to multiple congenital abnormalities, including cardiovascular defects. The gene(s) responsible for these disorders is thought to reside in a 1.5-Mb region of 22q11 in which 27 genes have been identified. We have used Cre-mediated recombination of LoxP sites in embryonic stem cells and mice to generate a 550-kb deletion encompassing 16 of these genes in the corresponding region on mouse chromosome 16. Mice heterozygous for this deletion are normal and do not exhibit cardiovascular abnormalities. Because mice with a larger deletion on mouse chromosome 16 do have heart defects, the results allow us to exclude these 16 genes as being solely, or in combination among themselves, responsible for the cardiovascular abnormalities in velocardiofacial/DiGeorge syndrome. We also generated mice with a duplication of the 16 genes that may help dissect the genetic basis of “cat eye” and derivative 22 syndromes that are characterized by extra copies of portions of 22q11, including these 16 genes. We also describe a strategy for selecting cell lines with defined chromosomal rearrangements. The method is based on reconstitution of a dominant selection marker after Cre-mediated recombination of LoxP sites. Therefore it should be widely applicable to many cell lines.